The Effect of Prepayment Contract Frames and Feedback on Budgetary Slack: An Experimental Investigation - Rohma, Frida Fanani; Anita, Nur (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: This research investigates the effect of prepayment contract frames and feedback incentives in mitigating budgetary slack. Background Problems: Clawback is an incentive scheme based on the endowment concept that has recently drawn researchers’ concerns. The literature suggests emphasizing the endowment and loss aversion concepts. This research examines these two concepts with one test model. Novelty: This research presents the preliminary manipulation role of hybrid clawback as one of the prepayment contract frames that are smoother and without penalty provisions. This study also examines the interaction between the concept of endowment and loss aversion in one test model. Research Methods: This research applied a field experiment with a 3 × 2 between-subject design. Finding/Results: This research found that prepayment contract frames require motivation from an adequate formal control system through frequent feedback to mitigate the slack. The findings prove that the capability of prepayment contract frames to minimize slack would be more effective after the frequency of the feedback has been moderated. Conclusion: The hybrid clawback could be a smoother alternative compensation scheme that is just as effective as a simple clawback, but without any penalty provisions. The effectiveness of a low feedback frequency could be increased to equal the efficacy of a high feedback frequency when assisted by prepayment contract frames.